Food Security at the Village Level: Learning from Hargorejo Village as a Village for Reducing Food Insecurity in the Special Region of Yogyakarta - Pranaja, Kevin Arya (Dialogue : Jurnal Ilmu Administrasi Publik, 2023)
This study aims to analyze food security at the village level, especially in Hargorejo Village, because Hargorejo Village has made achievements in reducing food insecurity in Yogyakarta. Thus making Hargorejo Village a pilot village for food security for other villages, especially villages still experiencing food insecurity. This study uses a descriptive qualitative research method, with a literature study using secondary data from the analysis of previous research and several mass media. Researchers used Webb and Rogers' food security theory to find out more details related to food security in Hargorejo Village. There are several indicators of food security: food availability, access, and absorption. The study's results stated that sweet potatoes were the most dominant food supply in Hargorejo Village on the food availability indicator. With data from village food production in Kokap District, this village produced 2,777 tons of cassava per year, then on the food access indicator, in accessing food in Hargorejo Village. More dominant in using physical access than social and economic access. This is evidenced by the description, which shows that there is physical access in the form of opening new land and making reservoirs by the Village Head of Hargorejo Village to supply the availability of food and clean water. Finally, on the food absorption indicator, it is noted that this village has a good record of nutrition and intake, as evidenced by the distribution table for the energy and protein adequacy consumption of rice and cassava by farm and non-farmer households.